Konseling Individu dengan Teknik De-Reflection untuk Mengurangi Kecemasan akan Kematian pada Lansia - Yati Oktavia; Kusnadi Kusnadi (Scidacplus, 2025)
The research is titled “The Application of Individual Counseling with the De-reflection Technique to Reduce Death Anxiety in the Elderly at Harapan Kita Nursing Home, Palembang.” This study aims to help the elderly reduce the anxiety experienced by three clients. Before the implementation of individual counseling with the de-reflection technique, the clients experienced excessive anxiety about death, as seen in their physical and psychological conditions. After the counseling sessions, the clients were better able to accept their situation. This research uses a qualitative approach with a case study method. The data collection techniques used were observation, interviews, and documentation. The subjects of this study were elderly individuals experiencing death anxiety at the Harapan Kita Nursing Home in Palembang. The results of the study showed that before receiving individual counseling, the clients tended to be quiet and had difficulty interacting with other elderly individuals. The individual counseling sessions using the de-reflection technique were conducted in four meetings, consisting of four stages: the initial stage, the middle stage (working stage), and the final stage. After the application of the de-reflection technique, the clients showed significant changes — they were able to accept the concept of death more calmly, no longer experienced excessive anxiety about death, and were able to socialize with fellow elderly individuals.